Adolescent intermittent ethanol (AIE) produces lasting, sex-specific changes in rat body fat independent of changes in white blood cell composition - Vore, Andrew S.; Marsland, Paige; Barney, Thaddeus M.; Varlinskaya, Elena I.; Landin, Justine D.; Healey, Kati L.; Kibble, Sandra; Swartzwelder, H. S.; Chandler, Lawrence J.; Deak, Terrence (Frontiers in Physiology, 2024)
Early initiation of alcohol use during adolescence, and adolescent binge drinking are risk factors for the development of alcohol use disorder (AUD) later in life. Adolescence is a time of rapid sex-dependent neural, physiological, and behavioral changes as well as a period of heightened vulnerability to many effects of alcohol. The goal of the present studies was to determine age-related changes in blood (leukocyte populations) and body composition across adolescence and early adulthood, and to investigate whether adolescent intermittent ethanol (AIE) exposure would alter the trajectory of adolescent development on these broad physiological parameters. We observed significant ontogenetic changes in leukocyte populations that were mirrored by an age-related increase in cytokine expression among mixed populations of circulating leukocytes. Despite these developmental changes, AIE did not significantly alter overall leukocyte numbers or cytokine gene expression. However, AIE led to sex-specific changes in body fat mass and fat percentage, with AIE-exposed male rats showing significantly decreased fat levels and female rats showing significantly increased fat levels relative to controls. These changes suggest that while AIE may not alter overall leukocyte levels, more complex phenotypic changes in leukocyte populations could underlie previously reported differences in cytokine expression. Coupled with long-term shifts in adipocyte levels, this could have long-lasting effects on innate immunity and the capacity of individuals to respond to later immunological and physiological threats.